Ten years of specialist training in Pediatrics at the Asociación Española HMO: main achievements and satisfaction levels of pediatricians (Archives of Pediatrics of Uruguay, 2020)
Introduction: training of specialists in Pediatrics accredited by the Graduate Medical School at Associated Training Centers (ATC) contributes to the decentralized training and continuous improvement process of quality of care.Objective: describe characteristics, academic progress and level of satisfaction of the residents at this ATC between 2009 and 2019.Materials and methods: variables: age, origin, marital status, number of children, chronic diseases, professional activities, number of courses passed, mandatory papers, final tests passed, research papers submitted to congresses, publications, residency period, sub-specialties. The characteristics and academic progress were obtained from files. The level of satisfaction was obtained from an anonymous voluntary online survey.Results: 24 residents were included during this period. 17 had finished curricular studies, 15 had obtained their degree, median age at the beginning of residency: 27 years, 5 were from the interior of the country, 15 had a stable partner, 9 had children and 9 had full-time positions at the institution. Regarding the present 7 residents, the median age at the beginning of residency: 26 years, all are from Montevideo, 5 have a stable partner, 1 has children and 6 have extracurricular activities. More than 70% of all responses assessed showed a high level of satisfaction.Conclusions: the experience of the last 10 years has been positive. It enabled the organization to obtain develop genuine highly committed human resources with institutional identity, good academic development and a high level of academic and job satisfaction.
Keywords: Pediatricians; Internship and residency; Job satisfaction